RESEARCH ON THE TYPES AND GENERAL CHARACTERISTICS OF DRY CONSTRUCTION MIXTURES (Web of Technology: Multidimensional Research Journal, 2025)
Every year, businesses dump hundreds of thousands of tons of waste into landfills, polluting the environment and negatively affecting the environmental situation. It is advisable to dispose of man-made waste that is harmful to the environment and use them wisely to improve the production of new types of building materials. The article is devoted to the analysis of works aimed at solving exactly these problems.